The Effect of Maggot and Silkworm on the Growth and Intestinal Histological Structure of Wader Pari Fish (Rasbora lateristriata Bleeker, 1854) - Devi Anisa Suci; Bambang Retnoaji (Jurnal Perikanan Universitas Gadjah Mada, 2023)
Wader pari is one of the fish that is often found in Indonesian waters. One of the problems regarding fish farming is the problem of feed. This study aims to determine the effect of alternative feeding on the growth and histological structure of the Wader pari fish's intestine. The paraffin method was used in constructing intestinal histological preparations by Haematoxylin-Eosin (HE) and Periodic Acid Schiff-Alcian Blue (PAS-AB) staining. Observations were done using the DMRT test on various ANOVA, and the histological structure of the intestine was analyzed descriptively and quantitatively. The treatments used in this study were P1 (commercial feed), P2 (maggot feed), and P3 (mixed feed between maggot and silkworms). The study's results indicated that the higher the protein consumed by the Wader pari fish, the higher the growth. The three treatments that affected the growth of Wader pari sequentially are mixed feed, maggot feed, and commercial feed. The histological structure of the wader pari intestine is composed of tunica mucosa, tunica submucosa, tunica muscularis, and tunica serosa. Maggot and mixed feed can affect the histological structure of the Wader pari intestine compared to commercial feed. This can be seen in the results of the length of the villi and the distribution of the number of goblet cells.